Alkaline Treatment effect on Teak Sawdust Aerogel in Waste Cooking Oil Adsorption: Pengaruh Perlakuan Basa Terhadap Aerogel Serbuk Kayu Jati Pada Adsorpsi Minyak Jelantah - Halawa, Arif Srimudaris; Salsabina, Syifa; Harfilani, Rialfi Putri Nur; Rizqita, Indy Inasa; Alghifari, Abudzar; Mitan, Nona Merry M. (Fakultas Teknik, Universitas Brawijaya, 2024)
Waste cooking oil is household waste that can pollute the environment and damage aquatic ecosystems if not properly treated. In Indonesia, its production reaches 6.46–9.72 million kiloliters per year. To address this issue, effective adsorbent materials such as cellulose aerogels are needed. This study utilizes teak sawdust waste as a cellulose source for aerogel production. The delignification process using NaOH yields cellulose pulp, which is then converted into cellulose aerogel. This cellulose aerogel was tested for its adsorptivity towards waste cooking oil, showing the highest absorption capacity at 100°C delignification variation, amounting to 0.27 grams of waste cooking oil per gram of cellulose aerogel with 76.15% of the waste cooking oil adsorbed. TGA analysis confirmed that the aerogel has higher thermal stability compared to the original teak sawdust waste, and SEM analysis revealed the porous structure of the aerogel supporting its adsorptive capacity. The results show that cellulose aerogel from teak sawdust waste is effective in absorbing waste cooking oil and has great potential as an environmentally friendly solution for water pollution, supporting Sustainable Development Goals (SDGs) Number 6 on clean water and sanitation.